Commelina Platyphylla - Grabiele, Mauro (2010)
Commelina platyphylla is a diploid species widely distributed in South America, representing a convenient model for karyological study. Different classical and molecular cytogenetics techniques were applied in order to evaluate its chromosomes. DAPI staining showed an unimodal and symmetrical karyotype (2A according to Stebbins, 1971) comprising 9m + 6sm medium-size chromosomes ranging from 2.29 to 4.04 µm, and 47.77 µm per haploid genome. In addition, CMA/Distamycin-A/DAPI fluorescence banding revealed the presence of two different types of constitutive heterochromatin (Hc), CMA+ DAPI (GC-rich) and CMA DAPI+ (ATrich), both comprising the 7.08% (3.38 µm) of the haploid genome. GC-rich Hc (42% of total) is exclusively NOR-associated, covering the entire terminal macrosatellite of chromosome pairs nos. 10 (sm) and 13 (sm). AT-rich Hc (58% of total) is localized interstitially (pairs nos. 4 and 12) or found at proximal (pairs nos. 2, 3 and 10) positions. Ag-NOR staining revealed 1 (77%) > 2 (19%) > 3 (3%) > 4 (1%) nucleoli in interphase nuclei and 1 (38%) > 2 (35%) > 3 (15%) > 4 (12%) active nucleolar organizer regions (NORs) in metaphase; nucleolar dominance of pair no. 10 vs. 13 (1.6 times) is observed by classical staining and confirmed by Ag-NOR and also nucleolar associated bodies (NABs) were recognized. Polymorphisms for cytological markers were not observed. The equilocal distribution of the different Hc blocks and NORs, its arrangement within the classical staining predicted suprachromosomal organization according to Bennett´s model added to the disposition of the chromocenters and the NABs in the interphase nuclei suggest concerted evolution for the Hc and NORs dispersion in C. platyphylla.